Islamic Considerations on the Application of Patient’s Autonomy in End-of-Life Decision - Malek, Mohammad Mustaqim; Rahman, Noor Naemah Abdul; Hasan, Mohd Shahnaz; Abdullah, Luqman (Springer, 2018)
In end-of-life situation, the need for patient’s preference comes into the picture with the intention of guiding physicians in the direction of patient care. Preference in medical directive is made by a person with full mental capacity outlining what actions should be taken for his health should he loses his competency. This is based on the reality of universal paradigm in medical practice that emphasises patient’s autonomy. A specific directive is produced according to a patient’s wish that might include some ethically and religiously controversial directives such as mercy killing, physician-assisted suicide, forgoing life-supporting treatments and do-not-resuscitate. In the future, patient autonomy is expected to become prevalent. The extent of patient autonomy has not been widely discussed among Muslim scholars. In Islam, there are certain considerations that must be adhered to.